An Experimental Study on Scale Effect in Dynamic Shear Properties of High-Damping Rubber Bearings - Murota, Nobuo; Mori, Takahiro (Frontiers in Built Environment, 2020)
High-damping rubber bearing (HDRB) is one of the most popular devices used for seismic isolation of structures. In order to clarify the mechanical characteristics of HDRB, various loading tests have been conducted on the bearings and obtained data have been applied to practical design of isolation systems. In this study, in order to investigate the scale effect on the physical characteristics of HDRB, dynamic loading tests were conducted with full scale and scaled model isolators, which have diameters of 1,000 and 225 mm, respectively. The test program covers shear strain dependence tests, frequency dependence tests, and repeated loading dependence tests. Special attention is paid in the differences of shear characteristics caused by the specimen scale. Repeated loading test was conducted only with a scaled model, and the relationship of temperature increase of the specimen and shear characteristics was evaluated. In parallel, finite element analysis (FEA) of the isolator under repeated loading was conducted. After the constitutive model of FEA was identified by the results, the FEA was extrapolated to simulate repeated loading of 1,000- and 1,600-mm-diameter isolators, which cannot be tested realistically by dynamic loading. Change of properties along the increasing number of cycles and temperature distribution of full scale and scaled down isolators were investigated. Necessity of consideration for the scale effect in the evaluation of HDRB properties by dynamic testing is discussed.